Investigation into the structure of spectra of signals with linear frequency modulatio - Gorbenko, I.D.; Zamula, A.A. (Radiotekhnika, 2018)
Analytical expressions for the spectrum and the uncertainty function for composite non-uniform signals with FM pulse width (SNLFM-FM signals) are obtained. The technique and results of studies of the SNLFM - FM signals spectral, correlation and structural properties are presented in the manipulation of the phase by various classes of binary discrete sequences.